Efficacy of rituximab in anti‐myelin‐associated glycoprotein demyelinating polyneuropathy: Clinical, hematological and neurophysiological correlations during 2 years of follow‐up. (25th September 2022) - Parisi, Mattia; Dogliotti, Irene; Clerico, Michele; Bertuzzo, Davide; Benevolo, Giulia; Orsucci, Lorella; Schiavetti, Irene; Cavallo, Roberto; Cavallo, Federica; Ragaini, Simone; Di Liberto, Alessandra; Ferrante, Martina; et al.
Abstract: Background and purpose: We evaluated the clinical and neurophysiological efficacy of rituximab (RTX) in a neurophysiologically homogeneous group of patients with monoclonal gammopathy and immunoglobulin M (IgM) anti‐myelin‐associated glycoprotein antibody (anti‐MAG) demyelinating polyneuropathy. Methods: Twenty three anti‐MAG‐positive polyneuropathic patients were prospectively evaluated before and for 2 years after treatment with RTX 375 mg/m 2 . The Inflammatory Neuropathy Cause and Treatment (INCAT) disability scale (INCAT‐ds), modified INCAT sensory score (mISS), Medical Research Council sum score, Patients' Global Impression of Change scale were used, IgM levels were assessed and extensive electrophysiological examinations were performed before (T0) and 1 year (T1) and 2 years (T2) after RTX treatment. Results: At T1 and T2 there was a significant reduction from T0 both in mISS and in INCAT‐ds, with a p value < 0.001 in the inferential Friedman's test overall analysis. Ulnar nerve Terminal Latency Index and distal motor latency significantly changed from T0 to T1 and in the overall analysis ( p = 0.001 and p = 0.002), and ulnar nerve sensory nerve action potential (SNAP) amplitude was significantly increased at T2 from T1, with a p value < 0.001 in the overall analysis. Analysis of the receiver‐operating characteristic curves showed that a 41.8% increase in SNAP amplitude in the ulnar nerve at T2 from T0 was a fair predictor of a mISS reduction of ≥2 points (area under the curve 0.85; p = 0.005; sensitivity: 90.9%, specificity: 83.3%). Conclusions: This study suggests that RTX is effective in patients with clinically active demyelinating anti‐MAG neuropathy over 2 years of follow‐up, and that some neurophysiological variables might be useful for monitoring this efficacy. Abstract : This study suggests that rituximab is effective in 23 patients with clinically active demyelinating anti‐myelin‐associated glycoprotein antibody neuropathy over a 2‐year follow‐up, and that some neurophysiological variables might be useful for monitoring this efficacy. Ulnar nerve Terminal Latency Index and distal motor latency significantly change after 1 year and ulnar nerve sensory nerve action potential (SNAP) amplitude significantly increased after 2 years. Analysis of the receiver‐operating characteristic curves showed that a 41.8% increase in SNAP amplitude of ulnar nerve at T2 from T0 was a fair predictor of modified inflammatory neuropathy cause and treatment sensory score reduction of ≥2 points.